Nanomaterials Manipulate Macrophages for Rheumatoid Arthritis Treatment - Li, Shuang; Su, Jin; Cai, Wei; Liu, Jian-xin (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic, progressive, and systemic inflammatory autoimmune disease, characterized by synovial inflammation, synovial lining hyperplasia and inflammatory cell infiltration, autoantibody production, and cartilage/bone destruction. Macrophages are crucial effector cells in the pathological process of RA, which can interact with T, B, and fibroblast-like synovial cells to produce large amounts of cytokines, chemokines, digestive enzymes, prostaglandins, and reactive oxygen species to accelerate bone destruction. Therefore, the use of nanomaterials to target macrophages has far-reaching therapeutic implications for RA. A number of limitations exist in the current clinical therapy for patients with RA, including severe side effects and poor selectivity, as well as the need for frequent administration of therapeutic agents and high doses of medication. These challenges have encouraged the development of targeting drug delivery systems and their application in the treatment of RA. Recently, obvious therapeutic effects on RA were observed following the use of various types of nanomaterials to manipulate macrophages through intravenous injection (active or passive targeting), oral administration, percutaneous absorption, intraperitoneal injection, and intra-articular injection, which offers several advantages, such as high-precision targeting of the macrophages and synovial tissue of the joint. In this review, the mechanisms involved in the manipulation of macrophages by nanomaterials are analyzed, and the prospect of clinical application is also discussed. The objective of this article was to provide a reference for the ongoing research concerning the treatment of RA based on the targeting of macrophages.